"Death Does Not Rot": Transitional Justice and Local "Truths" in the Aftermath of the War in Northern Uganda. Issue 2 (August 2013) - Meier, Barbara
The article looks at the way Acholi in northern Uganda address war-related matters of "peace" and "justice" beyond the mainstream human rights discourse reflecting some of the basic concepts that are decisive for the way people deal with transitional and local justice. The relationality and the segmentary structure of Acholi society play major roles in categorising "peace" and "war" while being at odds with the globalised standards of human rights that have been brought into play by international agencies, civil society and church organisations as well as the Ugandan state. A major argument is that a one-dimensional understanding of the cosmological underpinnings of rituals as a locally embedded tool of transitional justice (TJ) has an impact on the failure of TJ in northern Uganda. Thus the article highlights the specific cultural dilemmas in which the process of peace currently appears to be stuck.